Shipwrecks help invasive coral to expand range in the Atlantic Ocean - Soares, Marcelo de Oliveira (2020)
The invasive coral Tubastraea tagusensis (sun coral) is a habitat-forming species currently increasing its geographical range into the Atlantic Ocean, thereby causing negative ecological and socioeconomic impacts. Scuba divers observed this coral in the western equatorial Atlantic in January 2020, growing at high densities on a shipwreck from World War II (sunk in 1943) at a depth of approximately 32 m. Available footage from the beginning of the decade (2012–2018) shows no obvious signs of sun coral on this shipwreck, suggesting recent colonization and range expansion. The recent evidence of expansion was found 200 km east of the last record, which was also found on a WWII shipwreck (sunk in 1942) in 2016. We have identified hundreds of overlooked WWII shipwrecks, as well as new wrecks in shallow and mesophotic waters, that may provide stepping-stone habitats for this coral to expand its distribution in the Atlantic. We discuss the role of shipwrecks as a network of stepping stones for the sun coral spread, creating complementary paths for the invasiveness by overcoming physiological traits and the short lifespan of the coral larvae. Previous research underestimates the importance of these artificial stepping-stone patches in sustaining crucial dispersal events and range expansion of invasive species. These results are a call to action to manage the invasive Tubastraea corals at a national and international scale in the Atlantic basin.